Potential antibacterial effects of flaxseed and Nigella sativa extracts on 11 streptococcus pyogenes - Mustafa Al-Ahmad, Basma Ezzat; Mohamed Yusoff, Nurul Fatihah; Mustafa, Nazih Shaban; Subramaniam, Pram Kumar; Darnis, Deny Susanti; Mokhtar@Makhtar, Khairani Idah (Kulliyyah of Dentistry, International Islamic University Malaysia, 2020)
Antibiotic resistance is a major global problem, associated with inadvertent drug usage. Herbal interventions are a therapeutic strategy that warrants greater research attention. Flaxseed and Nigella sativa are well recognized original super foods that have demonstrated potent anti-microbial and anti-biofilm activities. In the oral cavity, the bacterial population is a result of the dynamic relationship between pathogens and commensals Streptococcus pyogenes is an important global human Gram-positive pathogen that causes a wide variety of acute infections, it is highly virulent since it has the ability overcome the host defence system. This in vitro study aims to evaluate antimicrobial activity of flaxseed and Nigella sativa extract against S. pyogenes. Ethanolic extract of flaxseed and Nigella sativa extracts were prepared and the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against S. pyogenes was estimated. The results of this study show that both extracts exhibited antibacterial activity against S. pyogenes. Present study demonstrated the bactericidal activity of both extracts which can be an adjunct to the future natural anti-bacterial therapy.